Effect of Chromium and Selenium-Eon Progesterone and Estradiol-17p Levels during Reproductive Cycle of Baladi Female Goats under Egyptian Conditions (Journal of Nuclear Technology in Applied Science, 2018)
The effect of chromium and selenium with vitamin E on progester) and estradiol-17 ~ (E) levels of Baladi female goats was theobjective of this study as new techniques for improving the reproductive perfonnance of Egyptian goats. Seventy-two of mature Baladi doeswere used through two conditions of mild and hot climates (36 animals/ season). The animals were randomly divided into three equal groups,is the control group, the 2 group was supplemented by chromiumin capsules and the 3 group was intramuscularly injected twice a weekwith 2ml VITESELEN®, (0.5 mg selenium and 10.7 IU vitamin E, Se-E).Serum honnones levels were assessed in the three experimental goats atthe estrous, pregnancy and postpartum periods. The results showed that Plevels during estrous cycle and mid-pregnancy periods were significantlyhigher in mild climate than in hot climate while opposite trend was foundduring early and late pregnancy as well as postpartum period. E levelsduring postpartum period were significantly higher in hot climate than inmild while during estrous cycle no significant differences in E2 levels dueto season. Chromium showed significant (P
Keywords: Chromium; Selenium-E; Heat Stress; Progesterone